2023
DOI: 10.3390/molecules28134910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steam on Carbonation of CaO in Ca-Looping

Abstract: Ca-looping is an effective way to capture CO2 from coal-fired power plants. However, there are still issues that require further study. One of these issues is the effect of steam on the Ca-looping process. In this paper, a self-madethermogravimetric analyzer that can achieve rapid heating and cooling is used to measure the change of sample weight under constant temperature conditions. The parameters of the Ca-looping are studied in detail, including the addition of water vapor alone in the calcination or carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It is hard to differ the reactivity of the residual coke increase or decrease as the carbon conversion increases. Based on the residual coke structure analyses, the graphitization degree decreased, and the surface area and pore volume increased, which would increase the reactivity, as reported [8,10,27]. Then, it could be concluded that the variation in the carbon and pore structure was not the key factor affecting the residual coke's reactivity.…”
Section: Residual Coke Reactivity Analysismentioning
confidence: 87%
“…It is hard to differ the reactivity of the residual coke increase or decrease as the carbon conversion increases. Based on the residual coke structure analyses, the graphitization degree decreased, and the surface area and pore volume increased, which would increase the reactivity, as reported [8,10,27]. Then, it could be concluded that the variation in the carbon and pore structure was not the key factor affecting the residual coke's reactivity.…”
Section: Residual Coke Reactivity Analysismentioning
confidence: 87%
“…The thermal decomposition, or calcination, of calcite has been extensively studied. Ratelimiting processes have been defined [1], and the effects of steam [2], pressure [3], CO 2 partial pressure [4], heating rate [5], and impurities [6][7][8], among other parameters, have been identified. Of the proposed calcination mechanisms, a mechanism involving intermediate "activated lime" CaO*(s), originally proposed by Hyatt et al in 1958 [9], has received support in more recent studies [4,10].…”
Section: Introductionmentioning
confidence: 99%